1989
DOI: 10.2307/145997
|View full text |Cite
|
Sign up to set email alerts
|

AFDC and the Formation of Subfamilies

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.. University of Wisconsin Press and The Board of Regents of the University of WisconsinSystem are collaborating with JSTOR to digitize, preserve and extend access to The Journal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

1994
1994
2003
2003

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(19 citation statements)
references
References 6 publications
0
19
0
Order By: Relevance
“…However, because that type of support is more verifiable than support from a cohabiting male, states are more likely to reduce the benefit in this case. The less-than-full taxation of parental support provides an incentive for a woman to live with her parents, as noted by Hutchens et al (1989). The fact that support is partly taxed provides a disincentive for a woman to live with her parents relative to a family-structure-neutral system in which the AFDC benefit is not affected by this type of family structure.…”
Section: Family Structurementioning
confidence: 99%
See 1 more Smart Citation
“…However, because that type of support is more verifiable than support from a cohabiting male, states are more likely to reduce the benefit in this case. The less-than-full taxation of parental support provides an incentive for a woman to live with her parents, as noted by Hutchens et al (1989). The fact that support is partly taxed provides a disincentive for a woman to live with her parents relative to a family-structure-neutral system in which the AFDC benefit is not affected by this type of family structure.…”
Section: Family Structurementioning
confidence: 99%
“…Ellwood and Bane (1985) found that higher AFDC benefits were associated with greater propensities for single mothers to live independently of parents, while Hutchens et al (1989) argued that the proper variable is the relative benefit between living with and without parents--equal to the benefit penalty imposed for living with parents--and found it to have a statistically significant effect on the propensity to live independently. Hu (2001) found that the probability that a teenager in a welfare family leaves the household is inversely related to the size of the benefit reduction suffered by the parent if the teen were to leave.…”
mentioning
confidence: 99%
“…These studies have found mixed results, depending partially on the definition of living arrangement utilized. Living arrangements have been defined in three ways in the literature to date: (1) using the Census Bureau's household head or subfamily head designation [Ellwood and Bane, 1985;Hutchens, Jakubson, and Schwarz, 1989;Winkler, 1992], 2 (2) creating a multilevel choice structure [Shelton and Sueyoshi, 1994], and (3) classifying single mothers into a few distinct groups without a multilevel choice structure [Folk, 1996;London, 1998;Hilton, 1995, Winkler, 1993]. The most recent studies tend to use the third type of classification, as it provides the most detailed information without imposing decision rules that are difficult to verify.…”
Section: Previous Researchmentioning
confidence: 99%
“…One set of studies does suggest that lower state AFDC benefit levels may be associated with family extension, especially in recent decades (Ellwood & Bane, 1985;Hendershott & Smith, 1989;Ruggles, 1997;Scheirer, 1983). However, Hutchens, Jakubson, and Schwartz (1989) found that the effects were small or nonexistent, Haurin, Hendershott, and Kim (1993) found that AFDC benefit levels had no relationship with whether women lived apart from parents (although AFDC levels did affect where the women lived once they had left: women who lived in states with higher AFDC levels tended to live alone rather than with others), and Whittington and Peters (1996) found that higher benefit levels were associated with a lower likelihood of young women-both mothers and non-mothers-leaving home for the first time. Gordon (1998) recently conducted a dynamic analysis that focused exclusively on young mothers.…”
Section: Predictors Of Minor Parents' Living Arrangementsmentioning
confidence: 99%